Phytochemical and Medicinal Potential of Genus Sonchus: A Review Article - Boukhary, Rima El; Assi, Ali Wassef; Hachichou, Assia Fadi; Nagar, Ali El; Ghalayini, Mohammad; Saab, Ahmad; Najm, Fathalla; Heidari, Rayan; Aboul-Ela, Maha (Pharmacognosy Reviews)
Genus Sonchus is a member of the Asteraceae family, contains several species that are well- known for both their medicinal properties and their extensive distribution throughout Europe, Asia, and Africa. The morphology, phytochemistry, and medicinal uses of Sonchus oleraceus and other prominent species are thoroughly reviewed in this article. Their potential as anti-inflammatory, antioxidant, antimicrobial, diuretic, antihypertensive, and cardioprotective agents has been highlighted by recent research. The findings demonstrate the pharmacological diversity of Sonchus species, confirming their traditional application and highlighting their importance in the development of contemporary drug discovery and Phytotherapy. First, a search was performed across different databases, including, Scopus, Science Direct, Google Scholar, The Cochrane Library, \Web of Science and PubMed from the year 2000 mostly till 2025. Second, articles were chosen based on specific related criteria as mentioned below. As this is a review article, we include most types of articles relevant to our subject and published in peer-reviewed journals. The search yielded 115 articles, and most of them were selected as the basis for the construction of the review. This literature review discussed the biological constituents and pharmacology of genus Sonchus. Based on the promising results collected in this manuscript, we recommend further research to be carried out on the extracts of plants of this genus for the extraction and identification of further molecules which can be helpful in medicine.
Keywords: S. oleraceus; Flavonoids; Hydroxycinnamic acids; Anti-cancer; Antimicrobial